Scoop - Allen, Woody 1935- (Madrid Onpictures, 2006)
At a turning point in his life, a former tennis pro falls for a femme-fatal type who happens to be dating his friend and soon-to-be brother-in-law.
Idiomas : Inglés, catalán y castellano. Subt.: catalán y castellano
Scarlett Johansson, Hugh Jackman, Jim Dunk
No recomendada para menores de 13 años
Keywords: Películas cinematográficas -- DVD